Madagascar : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in Madagascar during the 1990s. The paper highlights that Madagascar achieved financial stabilization in 1996 owing to the stepwise implementation of sweeping reforms that started in 1994 with the establishment of an interbank foreign exchange market. The paper focuses on selected aspects of Madagascar's medium-term economic strategy, deals with poverty issues in Madagascar, and provides an analysis of the Malagasy civil service and a strategy for its reform. The paper also examines Madagascar's trade regime and export processing zone.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet